An Analysis of Organizational Behaviour using k-Approximation Spaces - et. al., B. Praba, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rough set theory and Soft set theory are the two mathematical concepts that plays a vital role in decision making problems. In complex systems, the objects are equipped with various set of attributes and that will add the complexity in making decision. In this paper, we introduce k-approximation space and covering based k-soft approximation space that leads us to define k-rough set and covering based k-soft rough set. The significance of these two concepts are illustrated and compared in analyzing the Organizational behaviour of the employees in an Organization.